The Chronus Quantum software package. (10th September 2019) - Williams‐Young, David B.; Petrone, Alessio; Sun, Shichao; Stetina, Torin F.; Lestrange, Patrick; Hoyer, Chad E.; Nascimento, Daniel R.; Koulias, Lauren; Wildman, Andrew; Kasper, Joseph; Goings, Joshua J.; Ding, Feizhi; et al.
Abstract: The Chronus Quantum (ChronusQ) software package is an open source (under the GNU General Public License v2) software infrastructure which targets the solution of challenging problems that arise in ab initio electronic structure theory. Special emphasis is placed on the consistent treatment of time dependence and spin in the electronic wave function, as well as the inclusion of relativistic effects in said treatments. In addition, ChronusQ provides support for the inclusion of uniform finite magnetic fields as external perturbations through the use of gauge‐including atomic orbitals. ChronusQ is a parallel electronic structure code written in modern C++ which utilizes both message passing implementation and shared memory (OpenMP) parallelism. In addition to the examination of the current state of code base itself, a discussion regarding ongoing developments and developer contributions will also be provided. This article is categorized under: Software > Quantum Chemistry Electronic Structure Theory > Ab Initio Electronic Structure Methods Electronic Structure Theory > Density Functional Theory Abstract : The Chronus Quantum (ChronusQ) software package is an electronic structure software package specializing in time dependent and relativistic electronic structure theory written in modern C++.